PENGARUH KARAKTER EKSEKUTIF, KOMPENSASI RUGI FISKAL DAN CAPITAL INTENSITY TERHADAP PENGHINDARAN PAJAK - Ayu Safitri; Wiwit Irawati (Universitas Budi Luhur, 2021)
The research was intended to analyze the impact of the executive character, fiscal loss compensation and capital intensity against tax avoidance. This type of research is an assosiative quantitative using secondary data populations obtained from the Indonesian stock exchange and the 2016-2020 period company website of 23 companies. The sample retrieval technique on this study is by using purposive sampling method with the data analysis used is the regression data panel analysis by selecting the regression model, classic assumptions test and hypothetical analysis using data processing program Eviews 10. Based on the result of the test, the sudy states that: based on test of the executive character, fiscal loss compensation and capital intensity are simultaneously take effect by tax avoidance. Whereas by test T (partial) fiscal loss compensation affect tax avoidance, while executive character and capital intensity do not take affect tax avoidance.